-3-6v=-5(v-1)

Simple and best practice solution for -3-6v=-5(v-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-6v=-5(v-1) equation:


-3-6v=-5(v-1)

We simplify the equation to the form, which is simple to understand
-3-6v=-5(v-1)

Reorder the terms in parentheses
-3-6v=+(-5v+5)

Remove unnecessary parentheses
-3-6v=-5v+5

We move all terms containing v to the left and all other terms to the right.
-6v+5v=+5+3

We simplify left and right side of the equation.
-1v=+8

We divide both sides of the equation by -1 to get v.
v=-8

See similar equations:

| 2x-8=76-76 | | -2(b-6)+6=12-b | | y=12+5x | | □/15=35/5 | | 3=2f+5 | | -8(3n-4)=-25-5n | | 25x-7=9 | | y^2+12x+6y-27=0 | | (y-12)=5x | | m^2-9m-13=9 | | -4(-6-5x)=4x+24 | | 8x^2-2-18=-15 | | 1.25x+2y=50 | | 2r^2-3r+9=0 | | 12x-2=9x-4 | | 4-5/8(2) | | -6*(-7/2) | | Log[6](x-7)=2 | | 3n^2+6n-16=0 | | 4-5/8(-4) | | 4-5/8(6.5) | | 500x=5000 | | 4-5/8(-3) | | 11y+10x=3333 | | 5/2=-7w | | Y^2=15y-64 | | Y=-x(x-6) | | 4-x=7/3 | | 2a^2-9a=45 | | 0=x(x+7)(x-1) | | -5/2-5/3=-1/6u-7/2 | | 3n^2-11n=-1 |

Equations solver categories